ANALISIS PENGARUH SOCIAL MEDIA TERHADAP LOYALITAS PELANGGAN MELALUI BRAND IMAGE DAN BRAND AWARENESS - Husni, M. Fahrul (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This research aims to determine and analyze the influence of social media on customer loyalty through brand image and brand awareness. The analytical tool used in this research is data analysis using SEM-PLS. The population in this study was all followers of social media accounts with a total of 14,039 followers. The sampling technique used in this research was the Slovin technique, so the sample used was 100 followers of social media accounts from PT. A B C. The research results show that: (1) Social Media has a positive and significant effect on Customer Loyalty; (2) Social Media has a positive and significant effect on Brand Image; (3) Brand Image has a positive and significant effect on Customer Loyalty; (4) Social Media has a positive and significant effect on Brand Awareness; (5) Brand Awareness has a positive and significant effect on Customer Loyalty; (6) Social Media has a positive and significant effect on Customer Loyalty through Brand Image; (7) Social Media has a positive and significant effect on Customer Loyalty through Brand Awareness.